Clinical profile and molecular genetic analysis of alport syndrome in children: a single center experience - Ahmad, Aqsa; Lijun, Liang; Yan, Zhang; Yan, Ma; Shuai, Zhao; Wangnan, Du (Frontiers in Pediatrics, 2024)
BackgroundAlport syndrome (AS) is a multifaceted condition that primarily affects the basement membranes of the kidneys, ears, and eyes. AS is considered the second most common cause of hereditary renal failure, exhibiting varied clinical manifestations across different lifespans. The aim of this study is to investigate the clinical features and genetic profile of AS and to elucidate the genotype-phenotype correlation of AS.MethodThe clinical and genetic data of ten children with AS treated at the General Hospital of Ningxia Medical University between January 2021 and May 2024 were retrospectively analyzed.ResultsTen children with AS, six male and four female patients, with a mean age of 9 years (ranging from 3 to 15 years) were reported. Hematuria was observed in all individuals, with six cases exhibiting microscopic hematuria and four cases exhibiting macroscopic hematuria. Furthermore, extra-renal manifestations were noted in five cases, encompassing ocular abnormalities (n = 2) and hearing impairment (n = 3). In total, eight cases displayed mutations in COL4A5 indicating XLAS, while two cases manifested mutations in COL4A4 indicating ADAS. Nine different variants were detected, with 3 mutations identified as novel. Two cases underwent histopathological analysis, revealing a thin basement membrane and mild to moderate mesangial proliferation. Three cases were lost to follow-up, while the remaining seven maintained regular visits to our hospital. As of August 1st, 2024, the median follow-up time was 30 (range 24–36) months, and the renal function of the children under observation remained within normal parameters.ConclusionIn this study, the most commonly observed mutation was glycine substitution. Additionally, patients exhibiting severe mutations showed an increased vulnerability to complications, including proteinuria, ocular lesions, and hearing impairment. Genetic testing emerged as a critical resource for diagnosing AS. Furthermore, early diagnosis is crucial for implementing an appropriate management plan and assessing the prognosis.